STUDY OF ASSOCIATION OF STAGE WITH RESPONSE IN A PATIENT RECEIVING CONCURRENT CHEMO RADIOTHERAPY WITH 3 WEEKLY DOCETAXEL 45 MG/MT2 AND CISPLATIN 60 MG/MT2 IN LOCALLY ADVANCED TONGUE CARCINOMA - Nivedita Verma, Rajeev Ratan Jain, Umesh Dewangan, Manjula Beck , Vivek Choudhary , Pradeep Chandrakar , Rahul Swaroop Singh, Vikram Bali Rathore, Afreen Shams, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Head and neck carcinoma is a heterogeneous disease, encompassing a varietyof tumors that originate in the lip, oral cavity, hypopharynx, oropharynx Naso-pharynx, orlarynx.